Between a rock and a hard place: the shaping of employment in a global economy. (1st April 2010) - Ursula Huws
Abstract : Introducing this volume, this article discusses how employment practices are shaped in a global economy, asking to what extent national policies and institutions still play a role and the importance of other social, economic, political and cultural factors in determining how work is organised and the pay, conditions and job security of workers. Whilst it is clear that there are general tendencies of erosion of labour standards, fragmentation of labour and intensification of working time, it is also clear that workers in some occupations, industries and countries are better able to resist these tendencies than others. The papers in this issue present a range of theoretical and empirical research from across Europe that seek to explain these differences, with results that are also relevant for audiences in other parts of the world.